KARAKTERISASI: LIMBAH CAIR INDUSTRI TAHU DENGAN KOAGULAN YANG BERBEDA (ASAM ASETAT DAN KALSIUM SULFAT) - Bara Yudhistira; Martina Andriani; Rohula Utami (Caraka Tani: Journal of Sustainable Agriculture, 2016)
Tofu liquid waste can be further processed to produce some useful product. That can be kept anaerobically to produce some organic acid. The purpose of this study to know the microbial growth behavior characteristic of liquid tofu waste which produce with different production process, such as specific growth rate (m), doubling time (td), multiplication degree (n), product yield, and efficiency of acetic acid production. This study is also aimed to identify the acid type which produce with different production tofu process. The liquid waste which used for this study is obtained from tofu producer which uses acetic acid and calcium sulfate to coagulate the tofu protein. Liquid tofu waste was incubated 24 hour, in ambient temperature(30oC). analysis of total cell count, glucose concentration, acetic acid concentration, and pH value was evaluated in certain interval, such 0, 2, 4, 6 8, 10, 12, 14 16, 18, 20, 22, 24 hour. Acid type identification was evaluated in some phase during fermentation process. The observation result was plotted into a graphic which was shown the relationship of total cell count, with glucose concentration, acetic acid concentration, and also fermentation time. From the analysis of observation result, It can be concluded that, the specific growth rate of liquid tofu waste with acetic acid as protein coagulator is 0,3015/hour, while the specific growth rate of liquid tofu waste with calcium sulfate as protein coagulator is 0,2174/hour. The doubling time of liquid tofu waste with acetic acid as protein coagulator are 2,2991 hours, while the doubling time of liquid tofu waste with calcium sulfate as protein coagulator are 3,1877 hours. The multiplication degree of liquid tofu waste with acetic acid as protein coagulator are  2,605 times, while the multiplication degree of liquid tofu waste with calcium sulfate as protein coagulator are 1,880 times. The growth yield constant (Y p/s) of liquid tofu waste with acetic acid and calcium sulfate as protein coagulator respectively 8,1 x 109 cfu/mg and 8,1 x 107 cfu/mg. The product yield constant (Y p/s) of liquid tofu waste with acetic acid and calcium sulfate as protein coagulator respectively 1,7237 and 0,0306. The efficiency of acetic acid production during fermentation of liquid tofu waste with acetic acid and calcium sulfate as protein coagulator respectively 15,1376% and 2,5699%. Acid type identification shows that acid which was contained in liquid tofu waste recognized as Acetic acid.